2010
DOI: 10.1016/j.humimm.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Variant in CD209 promoter is associated with severity of liver disease in chronic hepatitis C virus infection

Abstract: CD209, a c-type lectin expressed by dendritic cells (DCs) acts as a pathogen recognition receptor. A single nucleotide polymorphism (SNP) in the promoter region of CD209 (-336 A/G; rs4804803) affects transcription and is associated with the severity of Tuberculosis and Dengue fever. As CD209 binds Hepatitis C Virus (HCV) glycoprotein-E2, we investigated this SNP in the context of chronic HCV infection.131 Irish women who had received HCV contaminated Anti-D immunoglobulin and 79 healthy controls were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Human clinical trials aimed at investigating the efficiency of PD-1/PD-L1 modulation in a variety of diseases, including HCV infection, are underway. The polymorphisms of the pattern recognition receptor expression, such as CD209, in DCs correlated with liver fibrosis scores and levels of ALT, as shown by Ryan et al [46] in a longitudinal study setting. Conversely, the polymorphism of DC-SIGNR, which is a CD209 ligand, might affect HCV loads [47].…”
Section: Myeloid Dendritic Cellsmentioning
confidence: 63%
“…Human clinical trials aimed at investigating the efficiency of PD-1/PD-L1 modulation in a variety of diseases, including HCV infection, are underway. The polymorphisms of the pattern recognition receptor expression, such as CD209, in DCs correlated with liver fibrosis scores and levels of ALT, as shown by Ryan et al [46] in a longitudinal study setting. Conversely, the polymorphism of DC-SIGNR, which is a CD209 ligand, might affect HCV loads [47].…”
Section: Myeloid Dendritic Cellsmentioning
confidence: 63%
“…Similarly the -336G allele was associated with downregulation of the symptoms of a Dengue virus infection (de Oliveira et al, 2014). In addition, a SNP at -939 demonstrated an association with tuberculosis in Indonesian populations but not in Vietnamese populations (Kobayashi et al, 2011), whereas another SNP (rs4804803) increases liver disease severity during chronic HCV infection (Ryan et al, 2010). These data demonstrate the importance of DC-SIGN during various infectious diseases.…”
Section: Prrs In Health and Diseasementioning
confidence: 85%
“…In the population analyzed in this study, the observed allele frequency was 20.2%, which is similar to the frequency observed in European countries (P > 0.05). In an Irish population, for example, the frequency of allele -336G is 19% (Ryan et al, 2010). In Spain, the frequency varies between 20.8% in the north to 22% in the south (Núñez et al, 2006;DieguezGonzalez et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we described the frequency of CD209 SNP -336A/G in a population from Piauí State, located in northeastern Brazil. This SNP has been associated with infectious diseases of different etiologies, notably those of viral origin (Kashima et al, 2009;Chan et al, 2010;Ryan et al, 2010;Wang et al, 2011;Barkhash et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation